Impact of Partial Root Drying and Soil Mulching on Squash Yield and Water Use Efficiency in Arid - Abdulhalim H. Farah; Hussein M. Al-Ghobari; Tarek K. Zin El-Abedin; Mohammed S. Alrasasimah; Ahmed A. El-Shafei (Agronomy, 2021)
Practical and sustainable water management systems are needed in arid regions due to water shortages and climate change. Therefore, an experiment was initiated in winter (WS) and spring (SS), to investigate integrating deficit irrigation, associated with partial root drying (PRD) and soil mulching, under subsurface drip irrigation on squash yield, fruit quality, and irrigation water use efficiency (IWUE). Two mulching treatments, transparent plastic mulch (WM) and black plastic mulch (BM), were tested, and a treatment without mulch (NM) was used as a control. Three levels of irrigation were examined in a split-plot design with three replications: 100% of crop evapotranspiration (ETc), representing full irrigation (FI), 70% of ETc (PRD70), and 50% of ETc (PRD50). There was a higher squash yield and lower IWUE in SS than WS. The highest squash yields were recorded for PDR70 (82.53 Mg ha−1) and FI (80.62 Mg ha−1). The highest IWUE was obtained under PRD50. Plastic mulch significantly increased the squash yield (34%) and IWUE (46%) and enhanced stomatal conductance, photosynthesis, transpiration, leaf chlorophyll fluorescence, and leaf chlorophyll contents under PRD plants. These results indicate that in arid and semi-arid regions, soil mulch with deficit PRD could be used as a water-saving strategy without reducing yields.